2017
DOI: 10.7448/ias.20.01/21358
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal longitudinal foreskin cut is associated with reduced risk of HIV, syphilis and genital herpes in men: a cross‐sectional study in Papua New Guinea

Abstract: Introduction: Various forms of penile foreskin cutting are practised in Papua New Guinea. In the context of an ecological association observed between HIV infection and the dorsal longitudinal foreskin cut, we undertook an investigation of this relationship at the individual level.Methods: We conducted a cross-sectional study among men attending voluntary confidential HIV counselling and testing clinics. Following informed consent, participants had a face-to-face interview and an examination to categorize fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…The best evidence to date for a potential role of the penile microbiome in sexually transmitted infections (STIs) and HIV acquisition have come from studies examining medical circumcision [5,6]. Male circumcision reduces the risk of HPV and HIV infection in men [7][8][9][10][11]. Male circumcision has been found to alter the penile microbiome by significantly reducing bacterial diversity and load [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The best evidence to date for a potential role of the penile microbiome in sexually transmitted infections (STIs) and HIV acquisition have come from studies examining medical circumcision [5,6]. Male circumcision reduces the risk of HPV and HIV infection in men [7][8][9][10][11]. Male circumcision has been found to alter the penile microbiome by significantly reducing bacterial diversity and load [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the prepuce by MMC significantly reduces the risk of STIs, including herpes simplex virus type 2 (HSV-2), syphilis, gonorrhea, HPV, and HIV ( 6 8 , 12 , 14 , 15 , 17 19 , 54 ). Three RCTs, conducted in South Africa ( 6 ), Kenya ( 7 ), and Uganda ( 8 ) observed that MMC reduced heterosexual HIV transmission in men without behavioral disinhibition (risk compensation behavior) by about 60%.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the protective effect of TMC on HIV infection are presumably due to variations in the age of coitarche (sexual debut) and amount of foreskin removed during circumcision ( 45 – 47 , 50 , 51 , 54 ). A study that assessed the variations in TMC practices and their association with HIV status among South African men observed that partially circumcised and uncircumcised men had the same risk for HIV infection, which was significantly greater than that of fully circumcised men ( 63 ).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, establishing a contemporary version of MICs will be in-line with a joint United Nations Educational, Scientific and Cultural Organization (UNESCO) and UNAIDS recommendation for HIV/AIDS education to include the teaching of life-skills and balanced gender roles [ 67 ]. Moreover, aligning MMC with a local cultural program would fulfil a PNG health priority for MMC to be made accessible for men who undergo high-risk foreskin cutting at non-clinical settings in PNG [ 68 – 70 ].…”
Section: Discussionmentioning
confidence: 99%